Pengaruh Kualitas Layanan, Ketersediaan Produk Wisata, Citra Destinasi Terhadap Kepuasan dan Loyalitas Wisatawan Kampung Karuhun Sumedang - Rina Trisnawati; Nono Wibisono (Jurnal Bisnis dan Kewirausahaan, 2022)
Sumedang Regency is an area that has various types of tourist attractions but tourist visits to Sumedang fluctuate every year. One of the attractions in Sumedang is Kampung Karuhun which still needs improvement in several aspects. This study aims to identify the influence of the relationship of service quality, tourism product availability, destination image, consumer satisfaction and destination loyalty in Kampung Karuhun Sumedang. The research method used is a quantitative approach using a survey tool in the form of a questionnaire. This study collected data as many as 355 respondents. The analytical technique used is descriptive analysis and Structural Equation Model (SEM) and the sampling technique used is purposive sampling. The results showed that service quality had a significant effect on consumer satisfaction and destination loyalty, the tourism product availability had no significant effect on consumer satisfaction but had an effect on destination loyalty. Furthermore, destination image has a significant effect on consumer satisfaction and destination loyalty. The last finding, consumer satisfaction has a significant effect on destination loyalty. Based on the results of the study, it can be concluded that the study offers evidence of the relationship between service quality, tourism products and destination image on tourist satisfaction and loyalty. The results of this study are expected to provide a tourism planning and marketing strategy in Karuhun Karuhun through an understanding that improving the quality of services, tourism products and destination image will increase tourist satisfaction and loyalty.